Cognitive Radio - Trump, Tonu (IntechOpen, 2017)
One of the most critical resources required for wireless communication is the radio spectrum. Traditionally, the administration of the spectrum rights tends to grant exclusive rights to some services in the major geographic regions. On the other hand, several studies have shown that the spectrum is actually underutilized and that new devices should use the underutilized spectrum in an opportunistic manner. Cognitive radio is a way to do that. The cognitive radio needs to collect cognition about the radio environment to operate efficiently. Such a radio needs to understand if the spectrum it intends to use is free or utilized by some primary user. By primary user we mean the licensed user of the band, and correspondingly the cognitive radios are often termed as secondary users. The goal of this book is to collect recent research about cognitive radio and provide an up-to-date review of the challenging topic.